2021
DOI: 10.12669/pjms.37.3.3274
|View full text |Cite
|
Sign up to set email alerts
|

Association amid the comorbidity of Diabetes Mellitus in patients of Active Tuberculosis in Pakistan: A matched case control study

Abstract: Objectives: This study aims to test the association between diabetes and tuberculosis. Methods: It is a matched case control study conducted in tertiary care hospitals in 2019-2020. Cases and controls were 144 each, selected on the basis of an odds ratio of 2 at 95% confidence interval with a significance level of 5%. Cases of pulmonary tuberculosis were selected through consecutive sampling technique, either visiting OPD or admitted in hospital. Controls were taken from the general population and freque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
(24 reference statements)
0
5
0
Order By: Relevance
“…Moreover, respondents were uncertain regarding the effects of diabetes on TB occurrence and treatment nonetheless, diabetes had been reported to be highly associated with tuberculosis previously. 23 On the one hand, pulmonary tuberculosis was recognized as a curable disease by majority of cases which was significantly different from non-TB group of this study. On the other hand, results showed that about 31% from non-TB group and 6% from TB group had poor knowledge regarding this aliment and not having any definite knowledge about TB prevention.…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Moreover, respondents were uncertain regarding the effects of diabetes on TB occurrence and treatment nonetheless, diabetes had been reported to be highly associated with tuberculosis previously. 23 On the one hand, pulmonary tuberculosis was recognized as a curable disease by majority of cases which was significantly different from non-TB group of this study. On the other hand, results showed that about 31% from non-TB group and 6% from TB group had poor knowledge regarding this aliment and not having any definite knowledge about TB prevention.…”
Section: Discussionmentioning
confidence: 51%
“…21,22 Khalid et al reported that TB patients in Pakistan were twice as likely to be malnourished than the healthy group. 23 TB group patients of the current study belonged to low socio-economic 3: Perception about TB treatment status and therefore might be malnourished as well as, we did not evaluate the physical status of the participants. This may explain our result that TB patients were more aware than the healthy respondents that malnutrition is a risk factor of TB.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, studies proved that the umbilical artery has a certain application value in the evaluation of fetal hypoxia. When fetal hypoxia occurs, the blood flow of the umbilical artery decreases significantly and the blood flow resistance index increases significantly [16][17][18] . The results of this study are consistent with those of the above investigators.…”
Section: Discussionmentioning
confidence: 99%
“… 1 With the recent socioeconomic development and lifestyle changes, ESRD has shown a rapid growth trend worldwide and has become a public health issue of global concern. 1 , 2 The estimated incidence of ESRD is currently 373.4 per million per year, and is associated with a heavy economic burden to patients and the healthcare system. 1 - 3 …”
Section: Introductionmentioning
confidence: 99%